(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2024)
Introduction: Breast lump is a very common problem among females attending surgical outpatient department. Its development and growth are under the control of various hormones and various physiological statuses like menstruation, pregnancy, lactation and menopause. Objectives: To evaluate the clinicopathological status of patients with non-inflammatory benign breast disease (NIBBD). Methods: This clinical study was conducted at the department of surgery, CMH Chattogram, this study was done during January 2018 to May 2019. Patient presented with breast lump, nipple discharge, sinus and mastalgia in whom histopathology revealed any type of non-malignant BBD were included in the study. Patient treated on outdoor patient basis were excluded and patient with malignant breast lesions or acute breast abscess requiring incision and drainage were excluded from the study. Results: Majority of the patients, 41(74.5%) had breast lump followed by 10(18.2%) had breast pain, 6(10.9%) had nipple discharge and 3(5.5%) had enlargement of breast. Most of the site was found unilaterally 54(98.2%). Majority of the patients, 27(49.1%) had fibroadenoma, 14(25.5%) had fibrocystic diseases, 10(18.2%) had fibroadenosis, 2(3.6%) had duct ectasia, 1(1.8%) had cystosarcoma Phyllodes and 1(1.8%) had Lipoma. Conclusion: Maximum age group was 3rd to 4th decade. Most of the patients clinically presented with lumps in the breast followed by pain, enlargement of breast, fever and nipple discharge. Mostly encountered breast lesion was fibroadenoma other common lesion were found fibrocystic diseases, fibroadenosis, duct ectasia, cystosarcomaphyllodes and Lipoma. JAFMC Bangladesh. Vol 19, No 1 (June) 2023: 27-30